Analisis Pengelolaan Data Rekam Medis Di Rumah SakitAngkatan Udara (RSAU) Lanud Iswahyudi - FARIDA, Maya Istia (2016)
Management of data in medical records in RSAU Iswahyudi Air Force Base still not coordinated and for some data processing such as assembling has not been implemented while the coding carried out by officers BPJS. The research objective is to analyze the coding, how to place the data management of patient registration at the Air Force Hospital (RSAU) Iswahyudi Air Force Base. Describe the management of medical patient data storage (filling), assembling, coding and reporting management in medical record Hospital Air Force (RSAU) Iswahjudi Air Force Base. This research uses descriptive qualitative research design. The population in this study medical records clerk. Sampling in this study conducted by purposive sampling. Validity test is done with tringulasi. The results showed there were shortcomings and weaknesses of the registration system, assembling implementation, implementation and implementation reporting coding.